Control And Stabilize System For Temperature In Operation Theatre By Using Microcontrolle - Ab Hadi, Nik Azran; Che Hasan, Mohd Hanif; Hashim, Nik Mohd Zarifie; Salleh, Azahari; Mohd Ab Halim, Mohd Firdaus (IJARET, 2015)
This project is to control and stabilize the temperature inside operation theatre.LM 35 will be placed inside the operation theatre that acts as a temperature sensor.It will give a signal to PIC16F876A to trigger the blower or heater. The temperature that is needed to be maintained is around - C.Therefore,once the LM 35 detects the minimum temperature,the heater will turn ON until the stable temperature is reached. The blower will continuously activate. However, when the maximum temperature is detected by the LM 35, it will send signals to the microcontroller. Thus,the microcontroller will control the speed of the blower. The system also will implement a new technology for air conditioning method. Block of ice will be used to supply the cold air inside the operation theatre. Thus,the blower will blow the block of ice to regulate the temperature. The system will be regulated continuously.